Prevalence and epidemiological trends in mortality due to COVID-19 in Saudi Arabia. (February 2023) - Alissa, D.A.; Aburas, W.; Almasuood, R.; Almudaiheem, H.Y.; Al Aseri, Z.; Alrabiah, F.; Ezzat, H.; Moulana, A.A.; Alawi, M.M.; Al-mutairy, E.; Alaama, T.; Alamri, M.S.; et al.
Abstract: Objectives: This article describes the prevalence and epidemiological trends of COVID-19 mortality in the largest registry in the Kingdom of Saudi Arabia (KSA). Study design: A prospective epidemiological cohort study using data from all healthcare facilities in KSA collected between March 23, 2020, and April 30, 2022. Data on the number of daily deaths directly related to COVID-19 were gathered, analyzed, and reported. Method: Data analysis was carried out using national and regional crude case fatality rate and death per 100, 000 population. Descriptive statistics using numbers and proportions were used to describe age, gender, nationality, and comorbidities. The mortality trend was plotted and compared with international figures. In addition, the most common comorbidities associated with mortality and the proportion of patients who received COVID-19 vaccine were reported. Results: The total reported number of deaths between March 23, 2020, and April 30, 2022, was 9085. Crude case fatality rate was 1.21%, and death per 100, 000 population was 25.38, which compared favorably to figures reported by several developed countries. The highest percentages of deaths were among individuals aged between 60 and 69 years, males (71%), and individuals with diabetes (60%). Only 2.8% of mortalities occur in patients who received COVID-19 vaccine. Diabetes, hypertension, and heart failure had the highest attributable risk of mortality among patients who died due to COVID-19. Conclusion: Case fatality rate and death per 100, 000 population in KSA are among the lowest in the world due to multiple factors. Several comorbidities have been identified, namely, diabetes, hypertension, obesity, and cardiac arrhythmias.